Evaluation of HIV health services in Lagos State: an empirical study. (1st January 2014) - Apena, Waliu; Bali, Rajeev K.; Binnersley, Jackie; Naguib, Raouf N.G.; Odetayo, Michael O.; Baskaran, Vikraman
This paper investigates the efficiency of a particular health service [specifically HIV/AIDS counselling and testing centres (HCT) in Lagos State, Nigeria]. A survey of 958 students, aged between 15–25, was carried out in Lagos State secondary schools and Lagos State University, in conjunction with the Lagos State Ministry of Education, Guidance and Counselling Unit. It was found that there was a low awareness about HIV testing and counselling activities in all the Lagos State divisions. This result suggests that Lagos State students remain vulnerable and that HCT centres are less organised than they could be and it proposes that knowledge management (KM) initiatives be adopted to increase both efficiency and effectiveness of efforts for this essential health service.